Executive control of stimulus-driven and goal-directed attention in visual working memory - Hu, Yanmei; Allen, Richard J.; Baddeley, Alan D.; Hitch, Graham J. (Attention, perception & psychophysics, 2016)
We examined the role of executive control in stimulus-driven and goal-directed attention in visual working memory using probed recall of a series of objects, a task that allows study of the dynamics of storage through analysis of serial position data. Experiment 1 examined whether executive control underlies goal-directed prioritization of certain items within the sequence. Instructing participants to prioritize either the first or final item resulted in improved recall for these items, and an increase in concurrent task difficulty reduced or abolished these gains, consistent with their dependence on executive control. Experiment 2 examined whether executive control is also involved in the disruption caused by a post-series visual distractor (suffix). A demanding concurrent task disrupted memory for all items except the most recent, whereas a suffix disrupted only the most recent items. There was no interaction when concurrent load and suffix were combined, suggesting that deploying selective attention to ignore the distractor did not draw upon executive resources. A final experiment replicated the independent interfering effects of suffix and concurrent load while ruling out possible artifacts. We discuss the results in terms of a domain-general episodic buffer in which information is retained in a transient, limited capacity privileged state, influenced by both stimulus-driven and goal-directed processes. The privileged state contains the most recent environmental input together with goal-relevant representations being actively maintained using executive resources.